Analytic Approximate Solutions to the Coupled Lotka-Volterra equations With Fractional Derivatives - Dahmani, Zoubir; Anber, Ahmed; Khati Bouraoui, Yasmina (International Journal of Nonlinear Sciences, 2010)
By introducing the fractional derivative in the sense of Caputo, we apply the Adomian decomposition method for the coupled Lotka-Volterra equations with time-and space-fractional derivative. As a result, numerical solutions are obtained in a form of rapidly convergent series with easily computable components. The behavior of Adomian solutions are shown graphically for some examples.
Keywords: Adomian method; caputo fractional derivative; coupled Lotka-Volterra equations